Zarys działalności Wydziału Kulturalno-Oświatowego Zarządu Obwodowego Związku Patriotów Polskich we Lwowie w latach 1944–1946 - Nowak, Rafał Kazimierz (Acta Universitatis Lodziensis. Folia Historica, 2013)
The article reveals the activity of Cultural and Educational Department of Polish Patriots Peripheral Management in Lvov since it was created in September 1944 till the time it was abolished in the mid of 1946. Officially the Department was divided into four sections: Press and Radio, Lecture and Reading, Scientific Section and Collections of book. There were also the committee and community events. The Department supervised as well the Little Forms Theatre called „Miniatury” as the Youth Sections till September 1945. The article presents the ventures of Peripheral Management in Lvov in the cultural and educational field. The ventures included such actions as taking part „Help Action” in Warsaw, collecting Polish books, creating common rooms for the young and organizing the Scientific Section and Radio Committee (since February 1, 1945 the people in Lvov could listen to Polish radio programs every day between 12 and 1 p.m.). The most imported initiatives of the Department were academies devoted to some important holidays and anniversaries like: Independence Day, May 1, May 3, Kościuszko celebrations, the anniversary of Lenino battle and October Revolution. The Department also supervised the actions of Little Forms Theatre „Miniatury” and was responsible for creating short articles which were to be published in „Czerwony Sztandar”. In the summary the autor noticed that the activity of Department in the field of Culture and Educational was a very important propaganda tool for members of Department. During the lectures and radio programmes taking into consideration the lack of access to a wide source of information, it was used to emphasize new thinking based on Polish and Soviet friendship. Nevertheless ceremonies created by the department despite the fact that they were permeated with propaganda ideas, gave the people in Lvov the strong feeling of affiliation to Polish Society and enabled them the wide access to Polish art, music, books and press.